Raising a rare girl : a memoir - Lanier, Heather Kirn (Penguin Press, 2020)
"The author's daughter was born with a very rare genetic syndrome and faced a daunting prognosis: she would be a fraction of normal size, have innumerable physical and mental difficulties and likely a shortened lifespan. Now, at age eight she is attending standard public school classes. This is the story of her family's journey"--